The role of community healthcare professionals in discussing sexual assault experiences during obstetrics and gynecological healthcare appointments - Andrea L. DeMaria; Stephanie Meier; Hannah King; Haley Sidorowicz; Kathryn C. Seigfried-Spellar; Laura M. Schwab-Reese (BMC, 2023)
Abstract Background Nearly half of adult women in the US report experiencing sexual assault, with almost one-fifth reporting rape. For many sexual assault survivors, healthcare professionals are the first point of contact and disclosure. This study aimed to understand how healthcare professionals working in community settings perceived their role in discussing sexual violence experiences with women during obstetrical and gynecological healthcare appointments. The secondary purpose was to compare healthcare professionals' perspectives with the patients' to determine how sexual violence conversations should occur in these environments. Methods Data were collected in two phases. Phase 1 consisted of 6 focus groups (Sept-Dec, 2019) with women aged 18-45 (n = 22) living in Indiana who sought community-based or private healthcare for women's reproductive healthcare needs. Phase 2 included 20 key-informant interviews with non-physician healthcare professionals (i.e., NP, RN, CNM, doula, pharmacist, chiropractor) living in Indiana (September 2019-May 2020) who provided community-based women's reproductive healthcare. Focus groups and interviews were audio-recorded, transcribed, and analyzed using thematic analyses. HyperRESEARCH assisted in data management and organization. Results There were three resulting themes: (1) healthcare professionals' approaches to screening for a history of sexual violence varied depending on how they ask, what setting they work in, and type of professional asking; (2) healthcare experiences can compound traumatic experiences and create distrust with survivors; and (3) sexual violence impacts patient healthcare experiences through what services they seek, how professionals may interact with them, and what professionals they are willing to utilize. Conclusions Findings offered insight into actionable and practical strategies for enhancing sexual violence screening and discussions in community-based women's reproductive health settings. The findings offer strategies to address barriers and facilitators among community healthcare professionals and the people they serve. Incorporating healthcare professional and patient experiences and preferences for violence-related discussions during obstetrical and gynecological healthcare appointments can assist in violence prevention efforts, improve patient-professional rapport, and yield better health outcomes.